La didactique de L2 à la croisée des chemins - Jean‑Paul Narcy‑Combes (Recherches en didactique des langues et des cultures)
This article reflects the point of view of a researcher in EFL teaching methodology who works in a French department. Although we might imagine that researchers in our field would actively seek each other out, institutional constraints create separations that are theoretically unjustified; Francophone research has an international scope, but remains somewhat cut off from Anglophone research in foreign-language teaching, no doubt to the detriment of both! The Acedle conference, bringing together colleagues from many different horizons, can serve as a forum for exchanges of information and ideas. We need a rigorous epistemological framework for these exchanges, since any domain where various theories co-exist will involve "translating" concepts from one field or school to another. We propose in this article to open various avenues of discussion, with epistemological proposals for what language-teaching methodology entails, and an identification of the theoretical problems facing our discipline. Three transductive relationships will be proposed as an operational theoretical framework. We will express this framework in terms used by several different schools of thought, to show that divergences within our discipline are often largely a matter of terminology. Examples of research methodology will be presented, to illustrate the difficulty of arriving at a rigorously-constructed, epistemologically sound object. Our conclusion will incite researchers to engage themselves as fully as possible in this scientific process.